The Alexiad of Anna Komnene : artistic strategy in the making of a myth - Buckley, Penelope, 1942- (Cambridge University Press, 2014)
"This is the first full-scale study of the literary art of Anna Komnene's Alexiad. Her history of her father's reign is well-known and much used by Byzantinists and historians of the First Crusade, but the art with which it shapes its central character has not been fully examined or understood. This book argues that the work is both history and tragedy; the characterization of Alexios I Komnenos is cumulative; it develops; the models for his idealization change; much of the action takes place in his mind and the narrative relays and amplifies his thought while building a dense picture of the world in which he acts. Engaging critically and responsively with other texts, Komnene uses the full range of current literary genres to portray the ideal culture of his rule. She matches her art of literary control to his of government over the adverse forces of his time"--